A clinical, comparative, prospective, and observational study of two different ratios of ketamine and propofol in short surgical procedures at a tertiary care hospital - Muralidhara KS; Shivakumar G; Santhosh MCB; Shashwatha N Gowda (Asian Journal of Medical Sciences, 2023)
Background: Ketamine and propofol are two medications commonly used for procedural sedation because they possess many of the desired characteristics including rapid induction and recovery. The opposing physiologic effects of ketamine and propofol suggest the potential for synergy, and this has led to an interest in their combined use, commonly termed “Ketofol.” The purpose of this study is to compare two different proportions of ketamine and propofol, 1:2 and 1:3 in short surgical procedures. Aims and Objectives: The aim of the study was to compare the quality of analgesia, level of sedation, and respiratory and hemodynamic parameters of two different proportions of ketamine and propofol in the ratio of 1:2 and 1:3 in short surgical procedures. Materials and Methods: After obtaining approval from the institutional ethics and scientific committee, with IEC no.MIMS/IEC/2021/474 dated February 23, 2021, 86 consenting patients of 18–60 years categorized under American Society of Anesthesiologists Category I and II undergoing elective short surgical procedures lasting for about 20 min were selected. The study patients were divided into two groups of 43 each by convenient sampling method. In Group A, 43 patients received 1 mL of ketamine (50 mg/mL) mixed with 10 mL of 100 mg propofol (10 mg/mL). In Group B, 43 patients received 30 mg of ketamine mixed with 9 mL of 90 mg propofol (10 mg/mL). Non-invasive blood pressure, heart rate, oxygen saturation, Ramsay Sedation Score, Modified Aldrete Score, and any incidence of side effects were recorded. Results: The quality of analgesia and level of sedation was achieved better in Group A compared to Group B. No significant difference was observed between the two groups with respect to hemodynamic and respiratory parameters. Conclusion: The combination of propofol and ketamine has several benefits such as hemodynamic stability, lack of respiratory depression, good recovery, and potent procedural analgesia. Ketofol 1:2 proportion is comparatively better and can be used safely in short surgical procedures.